PENGEMBANGAN MEDIA PERMAINAN MONOSHIKI UNTUK MENGENALKAN KEBIASAAN-KEBIASAAN YANG BERKAITAN DENGAN MUSIM SESUAI NENJUUGYOUJI - ANJARWATI, NAJDAH (HIKARI, 2020)
Abstract This study examines the development of monoshiki game media to introduce season-related habits according to nenjuugyouji. Based on a survey conducted by the Japan Foundation in 2015 which stated that globally, Indonesia was ranked second in the number of enthusiasts and institutions that learned and taught Japanese. However, the information provided is based on guidebooks both in formal and informal learning about habits related to seasons according to nenjuugyouji. Therefore the use of monoshiki game media to introduce habits related to the season in accordance nenjuugyouji. Monoshiki itself is a modified monopoly game, monopoly and shiki (four seasons). The way the game is almost the same as monopoly but with a few changes. This study aims to determine the process of making monoshiki game media and monoshiki game media user responses. This research uses Sugionos R&D (Research & Development) method. The research subjects were 6 people who had learned Japanese and those who did not learn Japanese at the product trial stage, and 20 people who had learned Japanese and people who had not learned Japanese in the trial use. Based on sources obtained from data from the media validation questionnaire monoshiki game obtained a percentage of 86.42% with very good criteria. Based on the results of the validation of monoshiki game material obtained a percentage of 70% with good criteria. Based on the acquisition of the percentage of media validation by media experts and the media validation by the monoshiki game material is appropriate to use with very good criteria to introduce about the four seasons based on nenjuugyouji in Japan for Japanese language learners. Based on data sources from 26 respondents who filled out the questionnaire responses of participants to the media game monoshiki obtained a percentage of 81.53% with very good criteria. Based on the results of the questionnaire responses of participants it can be concluded that the monoshiki game media got a good response from the participants. Keywords: Development, game, monopoly, culture, four seasons.